2019
DOI: 10.29333/ejmste/103047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Economic Inequality on Academic Achievement: The Black Boy Dilemma

Abstract: This study examined the effects of economic inequality on the academic achievement of the African-American males. African-American males are disproportionately poor, many living below the poverty line. The neighborhoods African-American males live in have few resources for learning which fosters low academic achievement. Predictions were made that African-American males in poor families will have lower academic achievement than white males and that African-American males who live in impoverished neighborhood e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Neighborhood disinvestment is associated with characteristics of classrooms that provide early childhood care and learning opportunities. Broadly, disinvested neighborhoods tend to have public schools that are characterized by low resources, lower graduation rates, lower teacher certifications, and dilapidated facilities ( Rothstein, 2013 ; Lynch, 2017 ; Pruitt et al, 2019 ). Neighborhood structural disadvantage has also been associated with lower quality of community child care programs ( Phillips et al, 1994 ; Fuller et al, 1997 ; Loeb et al, 2004 ; Burchinal et al, 2008 ) although public investment in high quality early education may mean that there is a somewhat higher prevalence of high quality programs in some of the most disadvantaged neighborhoods ( Phillips et al, 1994 ; Fuller et al, 2003 ).…”
Section: Mediating Pathways From Neighborhood To Self-regulationmentioning
confidence: 99%
“…Neighborhood disinvestment is associated with characteristics of classrooms that provide early childhood care and learning opportunities. Broadly, disinvested neighborhoods tend to have public schools that are characterized by low resources, lower graduation rates, lower teacher certifications, and dilapidated facilities ( Rothstein, 2013 ; Lynch, 2017 ; Pruitt et al, 2019 ). Neighborhood structural disadvantage has also been associated with lower quality of community child care programs ( Phillips et al, 1994 ; Fuller et al, 1997 ; Loeb et al, 2004 ; Burchinal et al, 2008 ) although public investment in high quality early education may mean that there is a somewhat higher prevalence of high quality programs in some of the most disadvantaged neighborhoods ( Phillips et al, 1994 ; Fuller et al, 2003 ).…”
Section: Mediating Pathways From Neighborhood To Self-regulationmentioning
confidence: 99%
“…These groups include, but are not limited to, girls (Foyn et al, 2018;He et al, 2020), LGBTQI+ children (Leyva, 2017;Rands, 2013), children from ethnically minoritized groups (Martin, 2019;Martin et al, 2015;Tabron et al, 2021), those whose home language is other than that of school and instruction (Chronaki & Planas, 2018;Moschkovich, 2018), children with intellectual, emotional, and kinesthetic disabilities (Cascales-Martínez et al, 2017;Watson & Gable, 2012), and those from low socioeconomic backgrounds (Chiu, 2018;Gates, 2019). In fact, things become more complicated when we consider marginalizing characteristics in intersectional manners (McLeman & Vomvoridi-Ivanovic, 2012;Pruitt et al, 2019). Stemming from the work of Crenshaw (1989), intersectionality, as an analytic framework, allows scholars in different fields to explore the structural interplay of variables such as race, class, gender, sexuality, and disability.…”
Section: Marginalization and School Mathematicsmentioning
confidence: 99%
“…Various research studies have been conducted on the selected factors, but literature displays that the socioeconomic status of the household was reliably found a strong predictor which affect educational results (Fan & Chen, 2001;Kushner, Benson, Mudrey-Camino & Steiner, 2010). Students' academic performance has been studied from various and multiple dimensions that children academic performance based on parenting style (Ahmed et al, 2019), students approach towards learning, educational services at schools and teachers assistances and capabilities (Maina, 2010), family socioeconomic position (Hanes, 2008;Pruitt et al, 2019), classroom learning setting, peer group, students inspiration and encouragement, home situation and parental participation in children education (Chen, 2018;Gustavsen, 2018), and partnership between school, family and community (Epstein, 2009). However, research studies found that the above mentioned factors have high influence on students' education and increases students' motivation to complete their academic responsibilities on time and develop their learning habits (WEF, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%